H2S Alleviates Salinity Stress in Cucumber by Maintaining the Na+/K+ Balance and Regulating H2S Metabolism and Oxidative Stress Response - Jiang, Jing-Long; Tian, Yun; Li, Li; Yu, Miao; Hou, Ru-Ping; Ren, Xu-Ming (Frontiers in Plant Science, 2019)
Salinity stress from soil or irrigation water can significantly limit the growth and development of plants. Emerging evidence suggests that hydrogen sulfide (H2S), as a versatile signal molecule, can ameliorate salt stress-induced adverse effects. However, the possible physiological mechanism underlying H2S-alleviated salt stress in cucumber remains unclear. Here, a pot experiment was conducted with an aim to examine the possible mechanism of H2S in enhancement of cucumber salt stress tolerance. The results showed that H2S ameliorated salt-induced growth inhibition and alleviated the reduction in photosynthetic attributes, chlorophyll fluorescence and stomatal parameters. Meanwhile H2S increased the endogenous H2S level concomitant with increased activities of D/L-cysteine desulfhydrase and β-cyanoalanine synthase and decreased activities of O-acetyl-L-serine(thiol)lyase under excess NaCl. Notably, H2S maintained Na+ and K+ homeostasis via regulation of the expression of PM H+-ATPase, SOS1 and SKOR at the transcriptional level under excess NaCl. Moreover, H2S alleviated salt-induced oxidative stress as indicated by lowered lipid peroxidation and reactive oxygen species accumulation through an enhanced antioxidant system. Altogether, these results demonstrated that application of H2S could protect cucumber seedlings against salinity stress, likely by keeping the Na+/K+ balance, controlling the endogenous H2S level by regulating the H2S synthetic and decomposition enzymes, and preventing oxidative stress by enhancing the antioxidant system under salinity stress.